Peran Supervisi Pendidikan yang Dilakukan Dinas dalam Meningkatkan Kinerja Kepala Sekolah di SMP Islam Terpadu At Tarbiyah Nagrak - Vikri Dwiki Sukandi; Siti Qomariyah; Ujang Ruslandi; Asep Rizkiyana (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
. This study aims to analyze the role of educational supervision conducted by the education office in improving the performance of school principals at SMP Islam Terpadu At Tarbiyah Nagrak. The research method employed is qualitative with a case study approach, where data is collected through in-depth interviews, observations, and document analysis. The findings indicate that educational supervision has a significant impact on the performance of school principals through managerial capacity building, monitoring of educational program implementation, and performance evaluation. The integration of Islamic values in supervision also strengthens the character of school principals as role models in applying Islamic values in the school environment. However, this study identifies several challenges, such as time constraints for supervision and a lack of understanding among supervisors regarding the context of integrated Islamic education. Recommendations include increasing the frequency and quality of supervision, providing special training for supervisors, and developing technical guidance for supervision based on Islamic values. This research is expected to contribute to the development of educational policies and supervisory practices in Islamic-based schools in Indonesia.